PENERAPAN HUKUM EKSEKUSI PENETAPAN IMBALAN JASA KURATOR YANG TIDAK SESUAI DENGAN PASAL 17 AYAT (2) UU K-PKPU - Theresia Simatupang; Rhonald Sianturi Hasudungan (Jurnal Dinamika Hukum, 2014)
Abstract This article discusses the execution of curator reward in terms of bankruptcy cancellation by Supreme Court in which Article 17 subsection (2) of Bankruptcy Law regulates that the decision is performed by the judge assembly on Final Appeal/Judicial Review. However, it is practically carried out by the judges of the Commercial Court. The method of this research is juridical normative. The result of this research indicates that the decision of curator reward execution in contrast with Article 17 subsection (2) of Bankruptcy Law could not be executed. Consequently, the injured party may take civil lawsuit, request for annulment of the decision to the Supreme Court or file judicial review. Key words: execution of judge decision, curator reward, bankruptcy cancellation